miR-344-5p Modulates Cholesterol-Induced β-Cell Apoptosis and Dysfunction Through Regulating Caveolin-1 Expression - Sun, Xulong; Ji, Guangnian; Li, Pengzhou; Li, Weizheng; Li, Jun; Zhu, Liyong (Frontiers in Endocrinology, 2021)
Diabetes is a metabolic disorder induced by the modulation of insulin on glucose metabolism, and the dysfunction and decreased number of islets β-cells are the main causes of T2DM (type 2 diabetes mellitus). Among multiple factors that might participate in T2DM pathogenesis, the critical roles of miRNAs in T2DM and β-cell dysfunction have been reported. Through bioinformatics analyses and literature review, we found that miR-344 might play a role in the occurrence and progression of diabetes in rats. The expression levels of miR-344-5p were dramatically decreased within cholesterol-stimulated and palmitic acid (PA)-induced rats’ islet β-cells. In cholesterol-stimulated and PA-induced diabetic β-cell model, cholesterol-caused and PA-caused suppression on cell viability, increase in intracellular cholesterol level, decrease in GSIS, and increase in lip droplet deposition were dramatically attenuated via the overexpression of miR-344-5p, whereas aggravated via the inhibition of miR-344-5p. miR-344-5p also inhibited cholesterol-induced β-cell death via affecting the apoptotic caspase 3/Bax signaling. Insulin receptor downstream MPAK/ERK signaling was involved in the protection of miR-344-5p against cholesterol-induced pancreatic β-cell dysfunction. Moreover, miR-344-5p directly targeted Cav1; Cav1 silencing could partially reverse the functions of miR-344-5p inhibition upon cholesterol-induced β-cell dysfunction, β-cell apoptosis, the apoptotic caspase 3/Bax signaling, and insulin receptor downstream MPAK/ERK signaling. In conclusion, the miR-344-5p/Cav1 axis modulates cholesterol-induced β-cell apoptosis and dysfunction. The apoptotic caspase 3/Bax signaling and MAPK/ERK signaling might be involved.